What to Expect When Youre Expecting: Femtoscopy at the LHC - Mike Lisa (Brazilian Journal of Physics, 2007)
A huge systematics of femtoscopic measurements have been used over the past 20 years to characterize thesystem created in heavy ion collisions. These measurements cover two orders of magnitude in energy, and withLHC beams imminent, this range will be extended by more than another order of magnitude. Here, I discusstheoretical expectations of femtoscopy of A+A and p+ p collisions at the LHC, based on Boltzmann andhydrodynamic calculations, as well as on naive extrapolation of existing systematics.